Effect of the g.98535683A > G SNP in the CAST gene on meat traits of Nellore beef cattle (Bos indicus) and their crosses with Bos taurus - Enriquez-Valencia, Cruz Elena [UNESP]; Pereira, Guilherme Luis [UNESP]; Malheiros, Jessica Moraes [UNESP]; Vasconcelos Silva, Josineudson Augusto I. I. de [UNESP]; Albuquerque, Lucia Galvao [UNESP]; Oliveira, Henrique Nunes de [UNESP]; Loyola Chardulo, Luis Artur [UNESP]; Curi, Rogerio Abdallah [UNESP] (Elsevier B.V., 2017)
The objective of this study was to estimate allele frequencies of the g.98535683A>G:BTAU7 SNP in the CAST gene in different genetic groups of beef cattle produced in Brazil (Nellore and their crosses with Bos taurus), and to evaluate associations between this polymorphism and meat traits. Five hundred animals from six different genetic groups were genotyped and phenotyped for shear force (SF), myofibrillar fragmentation index (MFI), rib eye area, backfat thickness, and total lipids. Alleles A and G of the SNP were detected in all genetic groups and the frequency of A was higher than G. Significant association (P < 0.05) was observed between the polymorphism and meat tenderness (SF and MFI), in which genotype AA exhibited the best values. These results demonstrate for the first time the occurrence of the studied SNP in a Zebu breed and its potential application to the genetic improvement of meat tenderness in the Nellore breed (Bos indicus) and its crosses with Bos taurus. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Calpastatin; Fat cover; Meat tenderness; Marbling; DNA polymorphism